The Tanytarsini (Diptera: Chironomidae) in the collection of the Museum of Amber Inclusions, University of Gdańsk - Zakrzewska, Marta; Giłka, Wojciech (Zootaxa, 2015)
Non-biting midges of the tribe Tanytarsini collected in the Museum of Amber Inclusions, University of Gdańsk, Poland, are reviewed. Among over 1500 chironomid specimens examined (inclusions in Baltic amber), 44 Tanytarsini individuals were found, of which 27 well preserved specimens were determined to 7 species, including 3 species described as new. Stempellinella electra sp. nov. (male) displays morphological hypopygial characters unique for the genus, and the antenna composed of 13 flagellomeres. A new checklist of fossil and extant species of this genus is also given, including Stempellinella sofiae (Fusari et Lamas, 2014) comb. nov. Tanytarsus glaesarius sp. nov. (male) is the only Eocene species of the genus with a reduced number of antennal flagellomeres. Tanytarsus protogregarius sp. nov. (male) is the oldest known representative of the gregarius species group. Notes on phylogenetic relations of the new species with their extant congeners are also provided.